2014
DOI: 10.3109/03009742.2014.882407
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the hand joints in patients with inflammatory bowel disease and arthralgia: a pilot study

Abstract: Several young IBD patients with chronic hand pain had subclinical inflammation on MRI, which invites for further study in a larger group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…On the other hand, if a patient did not present arthritis but only arthralgia during the clinical history, it is unlikely that bone erosions will develop. This is in agreement with previous studies performed on cohorts of patients with inflammatory arthritis and other diseases such as inflammatory bowel disease, in which erosions could not be detected by MRI [26].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, if a patient did not present arthritis but only arthralgia during the clinical history, it is unlikely that bone erosions will develop. This is in agreement with previous studies performed on cohorts of patients with inflammatory arthritis and other diseases such as inflammatory bowel disease, in which erosions could not be detected by MRI [26].…”
Section: Discussionsupporting
confidence: 93%
“…Arthritis is a common finding, and has been reported in 17–39 % of patients with IBD [ 6 ]. We found that the prevalence of joint alterations was as high as 48.8 %, although one magnetic resonance imaging (MRI) study of 11 IBD patients with painful hand joints without clinical synovitis and 11 without painful joints found no signs of synovitis in the latter [ 35 ]. However, the number of patients was small and the study only considered hand joints.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly sacroiliac joint alterations were not reported in the majority of examinations (112 [86%], 78 by MRI) [27]. A pilot study involving 11 IBD patients with arthralgia analyzed by hand MRI revealed, in two cases, the presence of enthesitis [28].…”
Section: Sacroiliac Jointmentioning
confidence: 99%